2021
DOI: 10.1159/000515124
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Dysfunction and Adverse Outcomes after Renal Transplantation

Abstract: <b><i>Introduction:</i></b> Pulmonary hypertension is common among patients with end-stage renal disease, although data regarding the impact of right ventricular (RV) failure on postoperative outcomes remain limited. We hypothesized that echocardiographic findings of RV dilation and dysfunction are associated with adverse clinical outcomes after renal transplant. <b><i>Methods:</i></b> A retrospective review of adult renal transplant recipients at a single instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…All included studies were observational and had a retrospective design [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies evaluated echocardiographic parameters as indirect markers of PH [ 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], while only one study included right heart catheterization in PH diagnostic algorithm [ 19 ]. PH was defined by using pulmonary artery systolic pressure (PASP) estimated by TTE in six studies [ 20 , 22 , 23 , 24 , 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All included studies were observational and had a retrospective design [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Most studies evaluated echocardiographic parameters as indirect markers of PH [ 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], while only one study included right heart catheterization in PH diagnostic algorithm [ 19 ]. PH was defined by using pulmonary artery systolic pressure (PASP) estimated by TTE in six studies [ 20 , 22 , 23 , 24 , 25 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…PH was defined by using pulmonary artery systolic pressure (PASP) estimated by TTE in six studies [ 20 , 22 , 23 , 24 , 25 , 27 ]. Right ventricular systolic pressure (RVSP), maximum tricuspid regurgitation jet velocity (TRJV), and right ventricular dilation and function were other TTE parameters used in clinical trials to estimate PH [ 18 , 21 , 26 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outside of the cardiac surgical setting, the prevalence of pre-existing RVD in surgical populations has seen limited study; however, what data does exist (Table 1) suggests a prevalence of anywhere between 5.7 and 100% and a profound effect on clinical outcomes. Prevalence figures naturally vary depending on patient population and definition of RVD -in the majority of studies, RVD is defined as 'normal' versus 'abnormal' on the basis of visual inspection on echocardiography images resulting in a relatively consistent estimate of the prevalence in the region of 5.7-11% (Chou et al 2021;Chou et al 2019;Joseph et al 2021;Meyer et al 2023). Reflecting an extreme estimate of incidence, Kim et al however examined RV function in 78 patients with mean age of 80.1 (9.1) years who had sustained a fractured hip and observed that RVD as defined by abnormal RV global longitudinal strain on 2D-speckle tracking was present in all (100%) patients (Kim et al 2017).…”
Section: Pre-existing Rvdmentioning
confidence: 99%
“…Reflecting an extreme estimate of incidence, Kim et al however examined RV function in 78 patients with mean age of 80.1 (9.1) years who had sustained a fractured hip and observed that RVD as defined by abnormal RV global longitudinal strain on 2D-speckle tracking was present in all (100%) patients (Kim et al 2017). Both pre-existing RVD and RV dilatation have been associated with increased incidence of complications and/or mortality in patients undergoing vascular, abdominal, orthopaedic, and renal transplant surgery (Chou et al 2021;Chou et al 2019;Joseph et al 2021;Kim et al 2017) (Table 1).…”
Section: Pre-existing Rvdmentioning
confidence: 99%